Workshop Peningkatan Kompetensi Pemrograman Web bagi Siswa Peserta Lomba Kompetensi Siswa SMK - Adisuputra Adisuputra; Aditya Ahmad Fauzi; Ditra Liandaputra; Fitriyanti Fitriyanti; Tri Dewi Yuni Utami; Dzalfa Tsalsabila Rhamadiyanti (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
The Student Competency Competition (LKS) in the field of Web Technologies for Vocational High Schools (SMK) demands a high level of web programming expertise aligned with the requirements of the modern digital industry. However, most participating students often face constraints in implementing clean code architecture, optimal performance, and W3C standardization validation. This community service activity aims to improve the technical web programming competence of vocational students who are prospective LKS participants through an intensive workshop delivery method. The partners for this service involve vocational students majoring in Software Engineering along with their mentoring teachers. The implementation method is systematically organized into three main phases, including prerequisite needs analysis, intensive training based on LKS jury standard modules, and independent project simulation evaluation. The results of the workshop implementation showed a significant increase in the technical capabilities of the participants, where the understanding of modern web architecture, basic security implementation, and compliance with code writing regulations experienced optimal improvement. Documentation of activities and students' portfolio work proves that the LKS jury criteria-based workshop approach is effective in preparing the mental and technical competence of the participants. The implication of this activity is expected to serve as a sustainable coaching model for schools to increase the competitiveness of vocational graduates in both regional and national competition events.